Model-Based Engineering for the support of Models of Computation: The Cometa Approach - Diallo, Papa Issa (Electronic Communications of the EASST, 2013)
The development of Real-Time Embedded Systems (RTES) increasingly requires the integration of several parts with different purposes. Consequently, the heterogeneous appearance of such systems creates a need to manage their growing complexity mainly due to the difficulty to interconnect the different parts composing them. Model-Based Engineering (MBE) has significantly participated in recent decades to find solutions in terms of methodologies and technical support tailored to the design of RTES. Indeed, several models are used to represent different aspects of the system. However, the interconnection of different modeling paradigms is still a difficult challenge. The handling of such problems requires a clear definition of the execution and interconnection semantics of the different models composing the system. Indeed, the abstraction of the execution semantics of machines or Models of Computation (MoC) can highlight properties for the whole system’s execution. In this paper, we propose an approach that captures these semantics at the earliest modeling phases with the aim of exhibiting properties that ease the design space exploration and performance analysis of systems. Our approach extends the Modeling and Analysis of Real-Time Embedded Systems profile (MARTE) by providing means to express communication semantics of models. We also review existing approaches for defining such execution semantics.